Identity and alterity in the consumption of foreign cultural products: the germans and the afro-brazilian capoeira - Rocha, Mariana Bussab Porto da (2019)
The frontiers between cultures and national economies have been pushed by the globalization movement, making the access to different ways of life easier and closer. The consumer then has available a truly global cultural supermarket, which places a multitude of cultural models at his/her disposal, where he/she can make choices for an identity-building project. The idea of cultural identity is anchored in the sense of belonging to a group, from an integration that will come through relation with similar people. The attraction for and the consumption of foreign cultural products seems to contradict consumers’ search for cultural identity. Cultural products are loaded with contextual and historical meanings and, therefore, are expressions and manifestations of folkways. They wide open the difference between groups. By using the German consumption of Afro-Brazilian capoeira (a fight dance) as context this thesis explores the reason why consumers from the more affluent world (MAW) adopt cultural practices originated in and impregnated by the culture of the other from the less affluent world (LAW) to express their own cultural identities. In order to explore that, this research has been divided into three sequential and complementary articles. Article 1 explores to what extent a product offered in the foreign market is the same as the one offered in the original market. The authenticity discussion is key in the internationalization of cultural products. Article 2 discusses more objectively the apparent paradox of the intention of building cultural identity through the consumption of foreign cultural products. The investigation of Article 2 failed to uncover a theoretical explanation, in the international consumer behaviour literature, for the foreign attraction to capoeira. Thus, the third article explores the potential exoticism has to help illuminate consumer behaviour in multicultural contexts, by including it as one positive consumer disposition towards foreign products. For the three articles, the author used an exploratory qualitative approach. Data was collected between 2015 and 2018, through three different methods: individual in-depth interviews, nonparticipant observation, and documents and audiovisual materials. The data was systematically transformed in results by the use of content analysis in an iterative, back-and-forth, reading process that kept uncovering patterns within and between informants and data sets, forming the major themes that helped to answer the study’s questions. Results pointed that once the foreign value of the cultural product has been preserved after internationalization, its authenticity is guaranteed in the host culture. It is precisely its difference that will attract the new consumer, however, it is the similarity that will keep him/her in this consumption. Consumers from countries from the MAW are interested in products from the LAW not just for being any sort of other, but an exotic other. Hence, exoticism can interfere with consumption choices, an idea which is expressed by the consumer exoticism construct proposal that refers to the attraction and the willingness to experience and consume different, culturally distant, foreign products.